Bank Mergers in the Emerging Markets : Are Market Returns to Merger Announcements indicative of Future Realised Gains in Performance? - Van Maanen, Floris (2005)
The purpose of this study is to examine the relationship between realised performance gains and short, intermediate and long-term market returns of target and bidder banks in Latin America and Southeast Asia. The results of this analysis find that markets in industrialised countries react differently to performance and transaction-specific variables for bidder and target banks. These differences arise for variables representing acquisition of control, industry concentration, and cross-border mergers. The results however, also find that stock transactions and firm size are not significantly related to share price changes for both acquiring and acquired firms. The analysis also finds that the explanatory power of market reactions to merger announcements tends to decrease with time in industrialised markets, and increase with time in emerging markets, indicating that market inefficiencies in emerging markets effect the ability for the stock market to accurate predict future performance gains. Although it is found that the market reaction to merger announcements is significantly related to reductions in operating expenses and gains in return on equity for both bidder and target banks, the results conclude that the market is not able to accurately predict overall performance gains within the first two years after a merger transaction.